Characteristics of high temperature co-gasification and ash slagging for Victorian brown coal char and bituminous coal blends. (1st March 2018) - Dai, Baiqian; Hoadley, Andrew; Zhang, Lian
Graphical abstract: Highlights: Brown coal char achieves a high carbon conversion even with a large particle size. Addition of 20% BCC to VBC char significantly promotes ash slagging. The slag film lowers the char conversion, but also reduces the production of metallic iron by wrapping unreacted carbon. Abstract: The low ash and high iron content of Victorian brown coal (VBC) makes it difficult to achieve desirable slagging for entrained-flow gasification. This study investigates the blending of VBC char with a high-ash bituminous coal for entrained-flow gasification. An industrially pyrolyised VBC char, a silica-rich bituminous coal char (BCC), and VBC char with BCC blends in three different blending ratios (20%BCC, 40%BCC and 80%BCC) are selected for high temperature gasification investigation in a lab-scale drop tube furnace (DTF) for temperatures ranging from 1000 to 1300 °C with different CO2 volume fractions. Scanning electron microscopy (SEM) coupled with elemental mapping, advanced synchrotron XANES and Mössbauer spectroscopy (MS) are employed to clarify the slagging propensity and iron transition behaviours during the blend co-gasification. It is found that VBC char, even in large sized particles, achieves a high char conversion and more than 50% CO fraction in syngas at 1300 °C, while BCC shows a lower char conversion and only 15% CO fraction in the same condition, due to only small particles being consumed. The blending of BCC into VBC lowers the char conversion compared to that of VBC alone due to the ash interactions. However, the element (Fe/Ca/Mg) loss during gasification reduces remarkably upon the addition of BCC, showing that the silica from BCC captures these elements. In addition, VBC generates more than 20% metallic iron out of total Fe-species during gasification, and the amount increases when temperature increases, which is undesirable for slag discharge. In contrast, blending 20% BCC with VBC char reduces α-Fe from 15% to about 7%, and reduces Fe3 O4 from 12% to less than 6%. This is because the silica in BCC can preferentially capture the iron-bearing compounds before they are reduced into metallic iron. Additionally, the unreacted carbon is covered by the slag, stopping it from reducing the Fe 2+ to metallic iron Fe 0 . The reduction of metallic iron is closely linked to the increase on the ash slagging extent, which is beneficial to slag discharge in entrained-flow gasifiers.